A time-scale adaptive dispatching strategy considering the matching of time characteristics and dispatching periods of the integrated energy system. (15th March 2023) - Wang, Xiaojing; Han, Li; Wang, Chong; Yu, Hongbo; Yu, Xiaojiao
Abstract: With the increasing proportion of renewable energy such as wind power accessing the grid, it is gradually difficult to deal with the renewable energy forecasting error only by conventional unit reserve. Facing the general rule that wind power forecasting error increases with the increase of forecasting step, it is necessary to explore a new strategy for integrated energy system dispatching with wind power integration. Recently, many new forms of energy have entered the field of vision, which provide new ideas for the renewable energy accommodation. However, the introduction of multi-energy with energy storage capacity requires to consider the time-coupling problem brought by their different time characteristics. At this time, it is difficult to take advantage of each system with fixed time-scale dispatching. Given the above problems, this paper proposes a time-scale adaptive adjustment strategy considering the matching of time characteristics and dispatching periods of the integrated energy system. Firstly, the time characteristics of wind power forecasting error and various energy systems in an integrated energy system are analyzed. Secondly, the energy storage equipment that can provide reserve in different time scales is determined according to their different response delay times. Finally, the system dispatching periods are dynamically adjust by comparing whether the system available reserve under the current time-scale is sufficient to compensate the wind power forecasting error under the current forecasting step. The proposed strategy achieves the matching of dispatching period, compensation equipment response time, forecasting step and forecasting error, improving the reliability of integrated energy system dispatching and its ability to cope with wind power uncertainty. Highlights: A time-scale adaptive adjustment strategy. The time-scale adaptive dispatching sub-main model. The matching of time characteristics and dispatching periods. The time characteristics of wind power forecasting error. The time characteristics of different energy systems in integrated energy system.